Regional Economic Study, Central Halmahera Regency, North Maluku Province - Tupamahu, Yonette Maya; Apituley, Margaretha Rosalyn (Agrikan: Jurnal Agribisnis Perikanan, 2021)
This study aims to determine the development potential in Central Halmahera Regency relative to North Maluku Province, to determine the components or elements of economic growth that have encouraged economic growth, and to determine the grouping of potential or superior economic activities. The analytical methods used are Location Quotient (LQ), Shift Share, Growth Ratio Model (GRM), Overlay analysis, and Klassen Typology.                   The results of the study show: 1) The main sectors and have the potential to be developed are the Manufacturing, Mining and Quarrying, Construction, Public Administration, and Defense; Compulsory Social Security sectors. 2) The Regional Share value reaches 52.74%, meaning that the economy of Central Halmahera Regency is quite dependent on the economic activities of North Maluku Province and the surrounding area. The regional superior economic potential according to the Proportional Shift component has a role of 6.73%. The contribution of Differential Shift is 40.53%, meaning that Central Halmahera Regency has special potential to drive regional economic growth. 3) The results of the GRM analysis show that the prominent sector growth in North Maluku and Central Halmahera Regency is the Electricity and Gas, Construction, Information and Communication, as well as Human Health and Social Work Activities. The results of the overlay analysis show that the sector is quite dominant so that it must get priority in development is the Construction Industry. The results of Klassen's Typology analysis show that the sector that is developing and growing rapidly is the Manufacturing and Construction Industry.